Ketahanan dan viabilitas probiotik bakteri asam laktat selama proses pembuatan kultur kering dengan metode freeze dan spray drying [Survival and Viability of Lactid Acid Bacteria Probiotic during production of Dried Culture Using Freeze and Spray Drying - Erni Harmayani; . Ngatirah; Endang S. Rahayu; Tyas Utami (Jurnal Teknologi dan Industri Pangan, 2001)
Selection on 36 lactid aid bacteria isolate from various source (dadih, sausage, infant faces, gato, chinese leaf pickle, growol and yoghurt) has been carried out based on their potency to reduce choresterol. Based on their ability to assimilate choresterol, conjugate bile solt, restency on bile salt and low pH, three isolates i.e. Lactobacillus sp. Dad 13, L. asidophillus D2 and L. plantarum Mut 7 have been chosen for further study. Viability of selected cultures during biomass production using coconut water with addition of 0.5% yeast extract, and during production of dried starter culture using freeze and spray dried were investigated. The results show that the growth patern of  the three isolates selected were almost similar i.e. reaching maximum amount after 16 hours fermentation at 37°C. biomass production using coconut water produced 109 cfu/ml after 16-18 hours incubation at 37°C. decrease on viability after drying using freeze drier ranged between 0.5-2 log cycles, while that of storage of freeze dried culture during 4 weeks at -20°C caused descreasing in viability of 26-56%.